Designing long-lived investments under uncertain and ongoing change - Klaus Eisenack; Marius Paschen (University of Oldenburg, Department of Economics, 2017)
Shall investments become more robust or more short-lived if unfavorable exogeneous conditions become more uncertain? What if the investments' design is irreversible for its whole life time? Such decision problems are frequently encountered, for example in infrastructure construction. We analyze this problem by combining an irreversible design decision when the investment starts with an irreversible decision to abandon an outdated investment. We formulate the second decision as a stopping problem of stochastic dynamic control, derive the value function, and the comparative statics for an optimal design. We find a decreasing optimal expected life-time and decreasing robustness for more rapidly changing conditions if the original life-time is not too large. For rising uncertainty, originally shorter-lived investments' life-times are expanded. For more long-lived investments, these effects may reverse. There can be a case for making investments less robust in the light of uncertain and ongoing change.
Keywords: 330